Kwestie sprzedaży ziemi rolniczej cudzoziemcom i implementacji wspólnej polityki rolnej w Polsce w negocjacjach akcesyjnych - Baborska, Bożena; Klimczak, Mikołaj; Narożny, Michał (Issues of Arable Land Acquisition by Foreigners and the Implementation of Common Agricultural Policy in Poland in the Course of Accession Negotiations, 2005)
The paper concentrates on two aspects of accession negotiations concerning the integration of Polish agriculture with the Single European Market. The first one regards the conditions of land acquisition in Poland, especially arable land, by citizen of the other European Union Member States. Arguments for and against establishing long transition periods in this matter are discussed. The second aspect applies to one of the most controversial problems of negotiations in the area of agriculture: the matter of full implementation of Common Agricultural Policy at the moment of the accession. Propositions of the EU are discussed with a special view at the future competitiveness of Polish agriculture, considering not yet predictable shape of the reformed CAP.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 129-145